Short-chain di-ureasil ormolytes doped with potassium triflate: Phase diagram and conductivity behavior - De Zea Bermudez, V.; Gomes Correia, S. M.; Silva, M. M.; Barros, S.; Smith, M. J.; Sá Ferreira, R. A.; Carlos, L. D.; Molina, C. [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Springer Nature, 2003)
Di-urea cross-linked poly(oxyethylene)/siloxane hybrids, synthesized by the sol-gel process and containing a wide concentration range of potassium triflate, KCF3SO3, have been analyzed by x-ray diffraction and differential scanning calorimetry. The pseudo-phase diagram proposed has been taken into account in the interpretation of the complex impedance measurements. The xerogels prepared are obtained as transparent, thin monoliths. At room temperature the highest conductivity found was 2 × 10-6 Ω-1 cm-1.
Keywords: Di-ureasils; Ionic conductivity; Phase diagram; Potassium triflate; Crosslinking; Differential scanning calorimetry; Doping (additives); Ionic conduction; Phase diagrams; Polyethylene glycols; Potassium compounds; X ray diffraction analysis; Ormolytes; Sol-gels